Thinking the world of work - Rivera Alfaro, Ronald (2020)
To think the world of the work from the social justice as political and socialconsideration allows to go deeply into the offer as into the labor demand, upto into the conformation of subjectivities and identities, productive transformations,historicity of the groups, and trends of the models of developmentwho stimulate the productivity and the employment, for example, on the otherhand, the constitution of spaces of domination and exploitation developedfrom the specialization of the means of production.